O Programa Digitmed e o conhecimento supradisciplinar na formação de pesquisadores-professores - Meaney, Maria Cristina (2024)
This research aims to discuss the extent to which the planning meetings of the Digitmed Program (PD), in their search for curricular decapsulation (Engeström, 2002; Liberali, 2019b, 2020b), that is, for bringing school practice closer to the life we live (Marx; Engels, 1845- 46/2006; Freire, 1970), reveal and challenge notions of knowledge/language and disciplinary segmentation. Based on the Theory of Socio-Historical-Cultural Activity (TASHC), I initially reflect on my professional career and the different conceptions of language and knowledge involved in it and how they moved me to investigate these concepts in the practices experienced in PD. Seeking to answer how the notion of school decapsulation was defined and pursued in the PD, I describe how it was organized and transformed throughout its history and analyze how the works produced from it understood the idea of school decapsulation (Engeström, 2002; Liberali, 2019b/2020b). Next, I define decapsulation from the holistic and complex perspective of human activity as the basis for the historical production of knowledge and language. In this sense, I consider the division of the curriculum into disciplines as a trace of coloniality and encapsulation (Quijano, 2005; Mignolo, 2017) and I defend the non-segmentation of knowledge as a decolonial and decapsulation movement, with human activity - integral, multisensory, contradictory and complex - as a microcosm of investigation. In an INdisciplinary way (Moita Lopes, 2006), I seek to base the non-fragmentation of knowledge on authors who questioned it from different fields of investigation, such as Paulo Freire (1978, 2011), Antônio Bispo dos Santos (2023) and David Bohm (2001). Based on an expanded view of language, as proposed in the perspective of Multiliteracies (The New London Group, 1996), I discuss knowledge as a typically human language, since it is the result of historical processes of meaning, of production of symbolic contents about the reality socially and culturally experienced. Considering other movements designed to overcome disciplinary fragmentation, I briefly discuss the efforts and limitations of multidisciplinary, interdisciplinary, transdisciplinary and INdisciplinary conceptions. I then point to supradisciplinarity as a possibility of understanding the holistic, complex, and unstable nature of knowledge/language, since it is produced in human activity. I then propose that human activity be the starting point of a truly integral education. Inserted in the theoretical-methodological perspective of Critical Collaboration Research (PCCol) (Magalhães, 2014), this research examined how the discussions that took place in planning meetings led to overcoming the coloniality of knowledge (Mignolo, 2017). The analysis sought to identify the conceptions of knowledge/language guided during the meetings as well as movements to decapsulate these notions. It revealed the contradictions (Marx; Engels, 1845- 46/2006; Magalhães, 2014) carried out by the PD teacher researchers. It thus made it possible to investigate the extent to which the experiences of these participants contributed to their sensitive understanding of the real problems experienced by society and their articulation with historically constructed knowledge and, from this, generate categories of analysis that point to conceptions and attitudes that decapsulate or reproduce a colonial structure. Furthermore, it illuminated PD as a locus of critical-collaborative training for these researcher-teachers